Development of a grape seed polyphenolic extract with anti-oligomeric activity as a novel treatment in progressive supranuclear palsy and other tauopathies - Pasinetti, Giulio Maria (2010)
A diverse group of neurodegenerative diseases — including progressive supranuclear palsy (PSP), corticobasal degeneration (CBD) and Alzheimer's disease (AD) among others, collectively referred to as tauopathies — are characterized by progressive, age-dependent intracellular formations of misfolded protein aggregates that play key roles in the initiation and progression of neuropathogenesis. Recent studies from our laboratory reveal that grape seed-derived polyphenolic extracts (GSPE) potently prevent tau fibrillization into neurotoxic aggregates and therapeutically promote the dissociation of preformed tau aggregates (Ho et al., 2009). Based on our extensive bioavailability, bioactivity and functional pre-clinical studies, combined with the safety of GSPE in laboratory animals and in humans, we initiated a series of studies exploring the role of GSPE (Meganatural-Az(®) GSPE) as a potential novel botanical drug for the treatment of certain forms of tauopathies including PSP, a neurodegenerative disorder involving the accumulation and deposition of misfolded tau proteins in the brain characterized, in part, by abnormal intracellular tau inclusions in specific anatomical areas involving astrocytes, oligodendrocytes and neurons (Takahashi et al., 2002). In this mini-review article, we discuss the biochemical characterization of GSPE in our laboratory and its potential preventative and therapeutic role in model systems of abnormal tau processing pertinent to PSP and related tauopathies.